2021
DOI: 10.1111/imr.12953
|View full text |Cite
|
Sign up to set email alerts
|

Human antiviral B cell responses: Emerging lessons from hepatitis B and COVID‐19

Abstract: Humoral immunity is a critical component of the coordinated response required to resolve viral infections and mediate protection following pathogen clearance or vaccination. A better understanding of factors shaping the memory B cell response will allow tailored development of efficient preventative vaccines against emerging acute viral infections, therapeutic vaccines, and immunotherapies for chronic viral infections. Here, we use recent data obtained by profiling antigen‐specific B cell responses in hepatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 112 publications
0
7
0
1
Order By: Relevance
“…The routes to FcRL5 expression and acquisition of an atypical memory phenotype are incompletely understood and likely context specific ( Burton and Maini, 2021 ). Our analysis of the data reported in Turner et al.…”
Section: Discussionmentioning
confidence: 99%
“…The routes to FcRL5 expression and acquisition of an atypical memory phenotype are incompletely understood and likely context specific ( Burton and Maini, 2021 ). Our analysis of the data reported in Turner et al.…”
Section: Discussionmentioning
confidence: 99%
“…The routes to FcRL5 expression and acquisition of an atypical memory phenotype are incompletely understood and likely context specific (Burton and Maini, 2021). Our analysis of the data reported in Turner et al (2020) found relatively low levels of FCRL5 transcript expression by GC B cells, suggesting that FCRL5 expression may be gained either by positively selected cells on their egress from the GC or by antigen-specific B cells after B:T cell interaction on the edge of the follicle.…”
Section: Discussionmentioning
confidence: 72%
“…However, a few studies have turned their attention to humoral immune responses, and thus investigated the role and function of B cells in the infection. 6 9 As in many other infectious diseases such as HIV, hepatitis B and malaria, 9 , 10 , 11 alterations of the B cell compartment have also been reported in COVID-19. 6 9 , 12 Interestingly, analyses of B cell populations revealed that extrafollicular double negative (DN) B cells, a characteristic of active systemic lupus erythematosus (SLE), 13 are a prominent feature of severe COVID-19 as well.…”
Section: Introductionmentioning
confidence: 91%
“… 6 9 As in many other infectious diseases such as HIV, hepatitis B and malaria, 9 , 10 , 11 alterations of the B cell compartment have also been reported in COVID-19. 6 9 , 12 Interestingly, analyses of B cell populations revealed that extrafollicular double negative (DN) B cells, a characteristic of active systemic lupus erythematosus (SLE), 13 are a prominent feature of severe COVID-19 as well. 7 , 12 , 14 , 15 Moreover, the frequencies of these DN cells correlate with disease severity profiles and some clinical and laboratory parameters of the disease.…”
Section: Introductionmentioning
confidence: 91%